Why is tractable vision loss in older people being missed? Qualitative study - Kharicha, Kalpa (BioMed Central, 2013)
BACKGROUND: There is compelling evidence that there is substantial undetected vision loss amongst older people. Early recognition of undetected vision loss and timely referral for treatment might be possible within general practice, but methods of identifying those with unrecognised vision loss and persuading them to take up services that will potentially improve their eyesight and quality of life are not well understood. Population screening does not lead to improved vision in the older population. The aim of this study is to understand why older people with vision loss respond (or not) to their deteriorating eyesight. METHODS: Focus groups and interviews were carried out with 76 people aged 65 and over from one general practice in London who had taken part in an earlier study of health risk appraisal. An analytic induction approach was used to analyse the data. RESULTS: Three polarised themes emerged from the groups and interviews. 1) The capacity of individuals to take decisions and act on them effectively versus a collection of factors which acted as obstacles to older people taking care of their eyesight. 2) The belief that prevention is better than cure versus the view that deteriorating vision is an inevitable part of old age. 3) The incongruence between the professionalism and personalised approach of opticians and the commercialisation of their services. CONCLUSIONS: The reasons why older people may not seek help for deteriorating vision can be explained in a model in which psychological attributes, costs to the individual and judgments about normal ageing interact. Understanding this model may help clinical decision making and health promotion efforts.